Progress in etching-driven MXene synthesis and utilization in conductive inks for printed electronics applications: A comprehensive review - Suriani Abu Bakar, Azmi Mohamed, Muhammad Noorazlan Abd Azis (Tanjung Malim, 2024)
Progress in etching-driven MXene synthesis and utilization in conductive inks for printed electronics applications: A comprehensive review by Suriani Abu Bakar, Azmi Mohamed, Muhammad Noorazlan Abd Azis